RANCANG BANGUN PROTOTYPE HYDRO TURBINE JENIS CROSS-FLOW UNTUK PERKOTAAN - Andrianus Andrianus; Steven Darmawan; Abrar Riza (Program Studi Teknik Mesin Universitas Tarumanagara, 2021)
The problem of fossil fuel crisis, both petroleum and coal, and the phenomenon of climatechange due to global warming, trigger the use of renewable energy that can overcome these problems.Cross-flow water turbine is one of the machine that can be used to produce small scale electric energy insmall scope. This turbine can be used in urban areas to assist industrial activities and their usefulness indaily life. The use of the right materials and strong construction can produce a good shape so that thiswater turbine is not only make efficient energy but also efficient and ergonomic in its use. This study isconducted theoretically to a cross-flow turbine which assumed to operate at 10m water height with 1.4L/s, outer diameter 150mm and 75mm thickness. The turbine consist of 15 blades with angle of attack ofthe blades is 30o. The results show that the turbine generate 119 Watt